Development of a Responsive Digital Intervention to Support Sexual Health Self-management and Quality of Life in Women with Breast Cancer - Calinca Eliotério Oliveira; Patrícia Brito Ribeiro de Oliveira; Camila Rangel Santos; Izabel Almeida Alves (Journal of Cancer Education, 2026)
Abstract Breast cancer is one of the most prevalent malignancies among women, and despite improved survival associated with endocrine therapy, treatment-related adverse effects significantly affect quality of life, particularly sexual health. This study aimed to describe the development of the responsive website “Cancer and My Life” , a digital self-management intervention designed to support the sexual health and well-being of women receiving oral endocrine therapy for hormone receptor-positive breast cancer. The development process followed the Medical Research Council framework for complex interventions and involved a multidisciplinary team, drawing on scientific evidence and relevant theoretical foundations. The resulting platform was developed as a responsive website and refined through iterative cycles of user testing and feedback. It provides educational content, psychosocial support tools, and interactive resources to promote autonomy, self-management, and informed decision-making. The website addresses topics identified through a comprehensive literature review, including body image, intimacy, genitourinary symptoms, and communication with partners. Overall, the platform demonstrates the potential of digital technology to deliver patient-centered support by addressing sensitive and frequently overlooked aspects of cancer care, such as sexual health, and highlights digital health as a promising strategy for more integrated and personalized oncology care.